Sarum : the novel of England - Rutherfurd, Edward (Ballantine Books, 2005)
Covering the entire course of English history, this epic follows five families that mirror the social and political forces that have shaped Britain--the Wilsons, the Masons, the Porteuses, the Shockleys, and the Godfreys. A masterpiece that is breathtaking in its scope, Sarum is an epic novel that traces the entire turbulent course of English history. This rich tapestry weaves a compelling saga of five families who preserve their own particular characteristics over the centuries, and offer a fascinating glimpse into the future.